IMPLEMENTASI ECO SCHOOL DALAM PROGRAM SURABAYA MENGAJAR UNTUK MENINGKATKAN KESADARAN LINGKUNGAN SISWA DI SDN BANYU URIP III/364 SURABAYA - Sabitha Ligar Suherman; Agung Pudjianto (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
The Surabaya Teaching Program is a form of community service that involves students as agents of change in supporting elementary school education. This community service activity was carried out at SDN Banyu Urip III/364 Surabaya for 4 months, aiming to increase students' environmental awareness through educational and practical approaches. Key activities included watering hydroponic plants using rice water, making organic fertilizer from fallen leaves, and processing cincau leaves into refreshing drinks. Each activity was designed to actively engage students, enabling them not only to understand basic concepts but also to practice environmental-based skills. The results of this program showed that students were able to apply environmental lessons in real-life situations, such as watering plants with natural materials, utilizing organic waste for fertilizer, and processing natural products into useful items. The program successfully increased students' awareness of the importance of environmental conservation while instilling values of sustainability and responsibility. This activity contributed not only to students' learning but also supported the school in creating a greener and more productive environment.